Erythrocyte sedimentation rate and C reactive protein in the assessment of polymyalgia rheumatica/giant cell arteritis on presentation and during follow up. Issue 8 (August 1989) - Kyle, V; Cawston, T E; Hazleman, B L
Abstract : The erythrocyte sedimentation rate (ESR) and C reactive protein (CRP) were measured in 74 patients with polymyalgia rheumatica (PMR)/giant cell arteritis (GCA) on presentation, in the first month of treatment, and at long term follow up (up to 177 weeks). Before treatment the ESR was raised (greater than 30 mm/h) in all cases and the CRP was raised (greater than 6 mg/l) in 49/55 cases. The ESR was a better indicator of clinical disease activity except in patients who felt completely well at week 1. 'False positive' increases of ESR or CRP were rare. During relapses ESR was normal in 37/77 (48%) of cases and CRP in 41/73 (56%). It is suggested that ESR is the most useful laboratory parameter in assessing PMR/GCA.